2013
DOI: 10.1016/j.jacc.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome Following Stringent Discontinuation of Dual Antiplatelet Therapy After 12 Months in Real-World Patients Treated With Second-Generation Zotarolimus-Eluting Resolute and Everolimus-Eluting Xience V Stents

Abstract: After 2 years of follow-up and stringent discontinuation of DAPT beyond 12 months, Resolute ZES and Xience V EES showed similar results in terms of safety and efficacy for treating patients with a majority of complex lesions and off-label indications for drug-eluting stents. (The Real-World Endeavor Resolute Versus Xience V Drug-Eluting Stent Study in Twente [TWENTE]; NCT01066650).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 32 publications
4
47
2
Order By: Relevance
“…In the randomized HOST ASSURE trial including 3755 all-comers patients comparing the EES and the ZES, TLF was 2.9% after one year in both arms (P ¼ 0.98) [16]. In the TWENTE trial 1391 patients were randomly treated with EES or ZES [17]. After 2 years the EES showed a significantly lower rate of target lesion revascularization (2.6 vs. 4.9%, P ¼ 0.03).…”
Section: Discussionmentioning
confidence: 99%
“…In the randomized HOST ASSURE trial including 3755 all-comers patients comparing the EES and the ZES, TLF was 2.9% after one year in both arms (P ¼ 0.98) [16]. In the TWENTE trial 1391 patients were randomly treated with EES or ZES [17]. After 2 years the EES showed a significantly lower rate of target lesion revascularization (2.6 vs. 4.9%, P ¼ 0.03).…”
Section: Discussionmentioning
confidence: 99%
“…All trials randomized the participants, and reported details of the randomization process used [6,7,[12][13][14]. All studies used methods of concealed treatment allocation adequately, except one [7].…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…Five published trials [6,7,[12][13][14] with a total of 9853 patients were included in our study. The number of patients in each study ranged from 650 to 3755 and the duration of follow-up varied from 12 to 48 months (mean duration, 21.6 months).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations